Понятійно-термінологічна система «Теорія конкуренції: конкурентність» - Соколова, Л. В. (The Academy of Management and Administration in Opole, 2015)
Problems in the theory of competition become very important in today's economic sphere of scientific communication. The purpose of the article: disclosure of conceptual and terminological system «Theory of Competition: Competitiveness» as one of the branch system of economics; determination of definitions and identification of relationships of its main structural elements. For the purpose achievement systematic approach to the specified system structure formation was proposed and the characteristic of its structural elements was provided. It is expedient and necessary to unite the creative efforts of the scientific community of the country towards the development of a certain terminological dictionary «Enterprise Competitiveness».
Formation of conceptual and terminological system “Theory of Competition: Competitiveness”
Keywords: теорія конкуренції; конкурентність; понятійно-термінологічний апарат